Biological and physicochemical stability of ceftazidime and aminophylline on glucose parenteral solution - Carolina Alves dos Santos; Laura Oliveira-Nascimento; Marcos Camargo Knirsch; Marco Antônio Stephano; Adalberto Pessoa Júnior; Thereza Christina Vessoni Penna (Universidade de São Paulo, 2012)
Ceftazidime is a broad spectrum antibiotic administered mainly by the parenteral route, and it is especially effective against Pseudomonas aeruginosa. The period of time in which serum levels exceed the Minimum Inhibitory Concentration (MIC) is an important pharmacodynamic parameter for its efficacy. One of the forms to extend this period is to administer the antibiotic by continuous infusion, after prior dilution in a Parenteral Solution (PS). The present work assessed the stability of ceftazidime in 5% glucose PS for 24 hours, combined or not with aminophylline, through High Performance Liquid Chromatography (HPLC). The physicochemical evaluation was accompanied by in vitro antimicrobial activity compared MIC test in the 24-hour period. Escherichia coli and Pseudomonas aeruginosa were the microorganisms chosen for the MIC comparison. The HPLC analysis confirmed ceftazidime and aminophylline individual stability on PS, while the MIC values were slightly higher than the mean described in the literature. When both drugs were associated in the same PS, the ceftazidime concentration by HPLC decreased 25% after 24 hours. Not only did the MIC values show high loss of antibiotic activity within the same period, but also altered MIC values immediately after the preparation, which was not detected by HPLC. Our results indicate that this drug combination is not compatible, even if used right away, and that PS might not be the best vehicle for ceftazidime, emphasizing the importance of the MIC evaluation for drug interactions. Ceftazidima é um antimicrobiano administrado por via parenteral, que apresenta amplo espectro de ação, principalmente contra Pseudomonas aeruginosa. O tempo em que a concentração sérica de ceftazidima permanece acima da concentração mínima inibitória (MIC) é um importante parâmetro farmacodinâmico para a determinação da eficácia antimicrobiana e pode ser potencializado através da utilização de infusão contínua em soluções parenterais (PS). Este artigo visa a avaliar a estabilidade da ceftazidima em solução de glicose 5%, na presença e na ausência do fármaco aminofilina, através de cromatografia líquida de alta eficiência HPLC e MIC durante o período de 24 horas. Os microorganismos selecionados para a determinação do MIC foram Escherichia coli e Pseudomonas aeruginosa. Os ensaios em cromatógrafo líquido confirmaram a estabilidade dos fármacos ceftazidima e aminofilina quando são individualmente associados em PS, enquanto os valores de MIC ficaram maiores que os valores encontrados na literatura. Quando ambos os fármacos foram associados na mesma solução parenteral a concentração de ceftazidima obtida por HPLC diminuiu 25% depois de 24 horas. Os valores de MIC mostraram maior decaimento da atividade antimicrobiana neste mesmo período e também valores de MIC alterados nas soluções preparadas no tempo zero, decaimento este que não foi detectado em HPLC. Os resultados indicaram incompatibilidade na associação dos fármacos em PS, enfatizando a importância dos resultados de MIC para interações de fármacos.